Polar Patrol Balloon (PPB) experiment data - Akira Kadokura (isOwnedBy)
The second campaign of the Polar Patrol Balloon (PPB) experiment was carried out during January to February, 2003 and during January to February, 2004. During the campaign periods, total four PPBs (PPB#7 to #10) were launched at Syowa Station. Three of the four (#7, 8, and 10) could reach ceiling altitudes and drifted westward around the Antarctica for 13, 25, 18 days, respectively. Instrument aboard #7 was the BETS (Balloon-borne Electron Telescope with Scintillating fibers) to observe the high energy primary cosmic-ray electrons. The instruments aboard #8 and #10 were the same as each other, consisting of the 3-axis electric field detector, 3-axis fluxgate magnetometer, auroral X-ray imager, GPS-TEC receiver, and ULF/LF band elecromagnetic wave receiver. #8 and #10 were launched successively on the same day to make a simultaneous observation at two adjacent location. Observed data were down-linked to the ground station, and at the same time, transferred to NIPR by using the Iridium satellite phone system.